Collateral blood vessels in acute ischemic stroke: a physiological window to predict future outcomes - Heitor Castelo Branco Rodrigues Alves; Felipe Torres Pacheco; Antonio J. Rocha (Arquivos de Neuro-Psiquiatria)
ABSTRACT Collateral circulation is a physiologic pathway that protects the brain against ischemic injury and can potentially bypass the effect of a blocked artery, thereby influencing ischemic lesion size and growth. Several recent stroke trials have provided information about the role of collaterals in stroke pathophysiology, and collateral perfusion has been recognized to influence arterial recanalization, reperfusion, hemorrhagic transformation, and neurological outcomes after stroke. Our current aim is to summarize the anatomy and physiology of the collateral circulation and to present and discuss a comprehensible review of the related knowledge, particularly the effects of collateral circulation on the time course of ischemic injury and stroke severity, as well as imaging findings and therapeutic implications.